2019
DOI: 10.3389/fonc.2019.00068
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Intraventricular Delivery of Therapeutic Neural Stem Cells to Orthotopic Glioma

Abstract: Neural stem cells (NSCs) are inherently tumor-tropic, which allows them to migrate through normal tissue and selectively localize to invasive tumor sites in the brain. We have engineered a clonal, immortalized allogeneic NSC line (HB1.F3.CD21; CD-NSCs) that maintains its stem-like properties, a normal karyotype and is HLA Class II negative. It is genetically and functionally stable over time and multiple passages, and has demonstrated safety in phase I glioma trials. These properties enable the production of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
(30 reference statements)
0
29
0
Order By: Relevance
“…Stem cells have been proposed in recent years for glioma therapy [168,169,170,171]. These cells have a tropism for brain tumoral tissue, a minimum tropism for normal neural cells, and the capability to cross the BBB [172,173,174,175,176].…”
Section: Stem Cells For Treatment Of Gbmmentioning
confidence: 99%
“…Stem cells have been proposed in recent years for glioma therapy [168,169,170,171]. These cells have a tropism for brain tumoral tissue, a minimum tropism for normal neural cells, and the capability to cross the BBB [172,173,174,175,176].…”
Section: Stem Cells For Treatment Of Gbmmentioning
confidence: 99%
“…Intraventricular administration has also been proven to result in good intratumoral distribution of stem cells [ 58 ]. Quantitative analysis and 3D reconstructions of the distribution of NSCs following intraventricular administration in mice demonstrated that these cells migrated efficiently toward tumors, even in the case of multifocal tumors located in different hemispheres [ 83 ]. NSCs tended to locate around the tumor margin but were also found within the tumor core.…”
Section: Routes Of Stem Cell Administrationmentioning
confidence: 99%
“…There are other case reports that have combined trastuzumab with other cytotoxic agents like methotrexate and/or cytarabine, resulting in prolongation of disease control in HER2+ brain tumor patients [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. In the preclinical setting, prophylactic IT administration of adeno-associated virus serotype 9 (AAV9) gene therapy vectors and tumor tropic neural stem cells (NSCs) loaded with chemotherapeutic agents shows that IT administration has the potential for efficient drug delivery of large molecules and biological vectors to the subarachnoid space [ 48 , 67 , 68 , 69 ].…”
Section: Invasive Technologiesmentioning
confidence: 99%